DETERMINAN MINAT MASYARAKAT MENJADI NASABAH ASURANSI SYARIAH DI JAKARTA - Muhammad Khusnul Fadlillah, (2023)
Human life has many risks so it requires a protection called insurance. Insurance in Indonesia only recognizes conventional insurance as time goes by, Sharia Insurance begins to be legalized. So that makes sharia insurance develop from time to time. Therefore, this research aims to describe and analyze the factors that influence people's interest in becoming sharia insurance customers in Jabodetabek. The research method in this study has a quantitative nature, and data collection uses primary data obtained by distributing questionnaires using a purposive sampling technique with 104 samples obtained from five different regions. The method used to analyze the data is a linear regression analysis technique using an analytical test tool, namely Statistical Product and Service Solution (SPSS). From this study, several hypotheses were obtained, namely product, promotion and religiosity variables affecting people's interest in becoming sharia insurance customers in Jabodetabek. Where the results of this study are that the promotion, product and religiosity variables have a significant effect on the interest of the Jabodetabek community to become sharia insurance customers. Furthermore, each variable partially and simultaneously has a significant effect on the interest of the Jabodetabek community to become sharia insurance customers.